The new CSS layout - Andrew, Rachel (A Book Apart, 2017)
CSS Grid Layout will transform the way you design and develop for the web- and Rachel Andrew will change the way you grok the spec. Learn to use Grid Layout within a system that includes existing methods to perform the tasks they were designed for-and take advantage of this pivotal moment in the evolution of layout.
Includes bibliographical references and index. - Online resource; title from cover (Safari, viewed June 4, 2018)
Keywords: Web site development; Cascading style sheets; Sites Web; Développement; Feuilles de style en cascade